The inter-related implications for Arctic Indigenous Peoples - Dorough, Dr. Dalee Sambo (Arctic Portal, 2011)
Dr. Dalee Sambo Dorough, University of Alaska Anchorage, USA, talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. The sessions name is Humanity, communities, Minds, Perceptions and Knowledge on Ice. Please click on the link above to see the video.